2022
DOI: 10.1523/jneurosci.2115-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Model of Sporadic Axonal Degeneration in the Drosophila Visual System

Abstract: In human neurodegenerative diseases, neurons undergo axonal degeneration months to years before they die. Here, we developed a system modeling early degenerative events in Drosophila adult photoreceptor cells. Thanks to the stereotypy of their axonal projections, this system delivers quantitative data on sporadic and progressive axonal degeneration of photoreceptor cells. Using this method, we show that exposure of adult female flies to a constant light stimulation for several days overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
(138 reference statements)
1
3
0
1
Order By: Relevance
“…Induction of the aln phenotype by the switch from LD to LL suggests an involvement of the circadian system, in line with the disruption of the circadian clock observed under sustained high light intensities 27 . Therefore, we wondered whether the Aln LL phenotypes may be mimicked in the per 01 circadian clock mutant.…”
Section: Resultssupporting
confidence: 55%
“…Induction of the aln phenotype by the switch from LD to LL suggests an involvement of the circadian system, in line with the disruption of the circadian clock observed under sustained high light intensities 27 . Therefore, we wondered whether the Aln LL phenotypes may be mimicked in the per 01 circadian clock mutant.…”
Section: Resultssupporting
confidence: 55%
“…To compare the number of retinal axon terminals–R7 axons–between genotypes, we used a previously developed automated method, MeDUsA ( me thod for the quantification of d egeneration us ing fly a xons) (Nitta et al, 2023). We have assessed the extent of their reduction from the total axonal terminal count, thereby determining the degree of axonal terminal degeneration (Nitta et al, 2023; Richard et al, 2022). Our results showed that the dOPA1 knockdown caused axonal degeneration one day after eclosion, further decreasing one week later (Figure 3B–E, quantification in 3F).…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila photoreceptors type R7/8 extend their retinal axons from the retina directly into the brain, forming synapses in the second optic ganglion medulla via the chiasma (Figure 1A), having potential application as a model for mammalian photoreceptors and RGCs. Based on this, we aimed to develop an experimental model for observing and quantifying degeneration in the Drosophila retinal axon (Nitta et al, 2023; Richard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Соответственно, мухи wимеют повышенную светочувствительность (Wu, Wong 1977), но недостаточную остроту зрения (Kalmus 1943). Другая функция белка white заключается в защите фоторецепторов сетчатки от чрезмерного воздействия света (Richard et al 2022). Данный ген экспрессируется в основном в пигментных клетках глаз, мальпигиевых канальцах и семен-никах (Evans et al 2008;Sullivan, Sullivan 1975).…”
Section: Introductionunclassified